Rural Schools and the Highly Qualified Teacher Provision of No Child Left Behind: A Critical Policy Analysis - Karen Eppley (Journal of Research in Rural Education, 2009)
While there is a growing body of work that considers the implications of the No Child Left Behind Act (NCLB) for rural schools, literature that critically examines the policy itself is lacking in rural educational research. This critical policy analysis focuses on the highly qualified teacher provision of NCLB as it relates to rural schools. The goal of critical policy analysis is to contextualize policy within its historical and political landscape, positioning policy as reflective of a group or individual's vision of an ideal society. While the highly qualified teacher provision has been advanced as unproblematic, critical analysis of its broader context suggests a mismatch between its assumptions and the unique needs of rural schools. While undoubtedly all children deserve a highly qualified teacher, what deems a teacher to be highly qualified is a matter that is both complex and highly context-dependent. Thinking about quality teaching in rural schools invites opportunity for dialogue, yet the provision reflects a reductionist, quantifiable conceptualization of quality. The policy stifles debate about what rural communities expect from their teachers, declaring consensus about the role of subject matter knowledge to the exclusion of other factors particularly salient in rural schools.